Precautions When Extracting Impacted Third Molars With Impacted Enamel Pearls in the Maxillary Sinus Floor: A Case Report - Hideki Suito; Yuuri Oku; Tomoyuki Kondo; Kumiko Kamada; Naito Kurio; Naoki Maeda (Clinical Case Reports, 2026)
ABSTRACT Cone‐beam computed tomography (CBCT) is routinely used before mandibular wisdom tooth extraction to determine its three‐dimensional relationship with the mandibular canal. In contrast, the extraction of a maxillary third molar is often planned based on panoramic radiographs alone. Enamel pearls are common at the maxillary molar sites, with prevalence varying by ethnicity; however, their detection based on panoramic radiographs alone is challenging. We herein present the novel case of a 27‐year‐old woman whose maxillary sinus floor was being elevated and partially perforated by enamel pearls, thereby increasing the risk of sinus perforation area spread, enamel pearl fracture, and displacement into the sinus cavity during extraction as well as postoperative complications. This case illustrates the clinical implications for the surgical management of impacted maxillary third molars located close to the maxillary sinus floor and also emphasizes the value of CBCT imaging for accurate preoperative assessment and surgical planning in such cases.